A Novel Technique to Retrieve a Maldeployed Vascular Closure Device. (February 2015) - Suri, Simrat; Nagarsheth, Khanjan H.; Goraya, Sumeet; Singh, Kuldeep
Purpose: To report a novel technique for endovascular retrieval of a maldeployed vascular closure device, obviating the need for a femoral cutdown.Technique: To remove a 6-F Angio-Seal device that embolized to the superficial femoral artery, the contralateral common femoral artery was accessed, and an 8-F, 65-cm-long sheath was inserted just proximal to the embolus. A second semistiff 0.035-inch buddy wire was advanced past the lesion along the sheath. A 0.014-inch wire was advanced past the embolus, and a SpiderFX embolic protection device was deployed 1 cm past the embolized Angio-Seal device. The sheath was advanced so as to push the embolus into the filter. The sheath and the filter containing the Angio-Seal device were then removed.Conclusion: Endovascular retrieval of an embolized Angio-Seal device can be done using an embolic filter device, restoring arterial flow to the limb.